Influence of change of hydraulic machine control parameter during braking of the tractor with the continuously variable transmission - Vadim Samorodov (Tehnologìčnij Audit ta Rezervi Virobnictva, 2017)
The influence of the hydraulic machine control parameter in the braking process of a wheeled tractor with a GMT is established. The relationship between the form of the change in the control parameter of the HMG hydrostatic machine and the kinematic, power and energy indicators of the wheeled tractor during braking is determined. The expediency of using the curved shape of the hydraulic control parameter change during braking due to the more effective intensity of the change is proved, which leads to a decrease in the braking and braking distances. The main disadvantage of this research is the need to confirm by experimental tests, obtained theoretically the results.